Victims as Subjects, Not Objects, in the Criminal Justice System - David Valencia; Mutiara Nefa Andini; Rifky Aditya; Ria Anggraeni Utami (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The criminal justice system has long tended to be offender-oriented, resulting in victims often being marginalized and viewed merely as objects within the evidentiary process. In reality, victims are the parties who directly suffer losses due to criminal acts and should, therefore, be positioned as subjects with legal rights and interests. This research aims to analyze the legal standing of victims within the criminal justice system and examine efforts to establish them as subjects from a victimological perspective. This study employs a normative legal research method with a statutory and conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal sources, which are analyzed qualitatively. The results indicate that although victims are normatively recognized as having rights, in practice, they are still frequently treated as objects within the criminal justice system. This is caused by a strong offender-oriented paradigm, a legal culture that does not yet favor victims, and limited mechanisms for victim participation in the judicial process. Consequently, a paradigm shift through victimological approaches specifically critical and restorative victimology is required to strengthen the position of victims as subjects within the criminal justice system.